2008
DOI: 10.1063/1.3037236
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect and Griffiths-like phase in La0.67Sr0.33MnO3 nanoparticles

Abstract: The effect of grain size on electrical and magnetic properties of La0.67Sr0.33MnO3 nanoparticles with average grain size 32–85 nm has been investigated. The metal-insulator transition temperature TP gradually decreases with decreasing grain size, while the ferromagnetic-paramagnetic transition temperature TC remains almost constant. For the 32 nm sample, the larger effective magnetic moments and the deviation of the inverse susceptibility from the Curie–Weiss law are observed, indicating the possible existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 27 publications
4
35
0
Order By: Relevance
“…The metal-insulator transition temperature (T MI ) was found to be 178 K. The lower value of T MI is due to a lower grain size, and the result is supported by the literature. 21 The T MI value is far below the corresponding T C value, associated with an apparent increase in resistivity. To this point, the reason for large discrepancy between T MI and T C is not known, and it has been stated that this huge discrepancy in nanostructured manganites is a mystery that requires a serious attention.…”
Section: Resistivitymentioning
confidence: 99%
“…The metal-insulator transition temperature (T MI ) was found to be 178 K. The lower value of T MI is due to a lower grain size, and the result is supported by the literature. 21 The T MI value is far below the corresponding T C value, associated with an apparent increase in resistivity. To this point, the reason for large discrepancy between T MI and T C is not known, and it has been stated that this huge discrepancy in nanostructured manganites is a mystery that requires a serious attention.…”
Section: Resistivitymentioning
confidence: 99%
“…1) and reaches 8 J/(kg K) for ∆H = 2 T. It is the highest value ever observed for doped LaMnO 3 manganites, larger than that known for gadolinium. The same compounds but in nanocrystalline form were studied in [24][25][26]. It was shown that value of |∆S H | in the nanocrystalline manganite is very small.…”
Section: Magnetocaloric Effect In Manganitesmentioning
confidence: 99%
“…Considerable investigations indicate that the nanostructured materials are very promising candidates for potential application in the magnetic refrigeration (Zhang et al 2001;Tanaka et al 2001;Hueso et al 2002;Provenzanoa et al 2003;Shir et al 2003;Kinoshita et al 2004;Evangelisti et al 2005;Poddar et al 2006;Gómez-Polo et al 2007;Ma et al 2007;Baldomir et al 2007;Franco et al 2007;škorvánek et al 2007;Poddar et al 2007;Biswas et al 2008;Franco et al 2008;Gorsse et al 2008;Li 2008;Gass et al 2008;Lu et al 2008;Santanna et al 2008;Serantes et al 2008;Pekała and Drozd 2008;Juan and Gui 2009;Gorria et al 2009;Phan et al 2009;Babita et al 2009;Calderon-Ortiz et al 2009;Das et al 2009;Phan et al 2010;Burianova et al 2010;Nelson et al 2002). However, up to now, not much effort has been devoted to the rare earth bulk nanocrystalline metals.…”
Section: Introductionmentioning
confidence: 99%